La reconceptualisation et l’adaptation d’expression en terminologie culturelle - Diagne, Abibatou (Linguistik Online, 2022)
The study focuses on two fundamental aspects developed in cultural terminology: (re)conceptualization and the adaptation of expression developed by Diki-Kidiri et al. (2008). They are means by which, in an African environment, in a context of weak terminological development, speakers of a language can reappropriate knowledge and adapt it to the possibilities of expression specific to that language. Reconceptualization and the adaptation of expression are complex processes although the authors (Diki-Kidiri et al. 2008) propose ways to achieve them. We recall the key elements of cultural terminology that support the (re)conceptualization and adaptation of expression. On the basis of recent studies in cognitive science (Carey 2009), we underline the limits of an approach based on the notion of percept and insist, following (Temmerman 2000), on the contribution of cognitive linguistics to terminology. The last point addressed concerns the formal aspect of terminological units which, in our opinion, should not only be popularized units, the objective being to move towards a cultural terminology beyond perception and popularization.